Co-encapsulation of magnetic Fe(3)O(4) nanoparticles and doxorubicin into biodegradable PLGA nanocarriers for intratumoral drug delivery - Jia, Yanhui (Dove Medical Press, 2012)
In this study, the authors constructed a novel PLGA [poly(D,L-lactic-co-glycolic acid)]-based polymeric nanocarrier co-encapsulated with doxorubicin (DOX) and magnetic Fe(3)O(4) nanoparticles (MNPs) using a single emulsion evaporation method. The DOX-MNPs showed high entrapment efficiency, and they supported a sustained and steady release of DOX. Moreover, the drug release was pH sensitive, with a faster release rate in an acidic environment than in a neutral environment. In vitro, the DOX-MNPs were easily internalized into murine Lewis lung carcinoma cells and they induced apoptosis. In vivo, the DOX-MNPs showed higher antitumor activity than free DOX solution. Furthermore, the antitumor activity of the DOX-MNPs was higher with than without an external magnetic field; they were also associated with smaller tumor volume and a lower metastases incidence rate. This work may provide a new modality for developing an effective drug delivery system.